Surface modification with lithium silicate to enhance the electrochemical performance of high-valence metal oxide compound MnTeMoO6. Issue 38 (14th September 2022) - Zhao, Xiangyan; Li, Bo; Zhuang, Ji; Liu, Chao; Zhu, He; Xue, Ni; Xue, Mei; Wang, Lei; Tao, Xutang
Abstract : MnTeMoO6 @Li2 SiO3 composite electrodes exhibit enhanced electrochemical performance with lower activation energy. Abstract : Surface modification is an effective technique to improve the electrochemical performance of electrode materials. However, although carbon coating is cheap and applicable, it is unsuitable for some high-valence metal oxide compounds due to the reduction of carbon. In this work, manganese tellurium molybdate, MnTeMoO6, was developed utilizing lithium silicate Li2 SiO3 coating as an extra solid-state electrolyte layer, and its electrochemical performance was investigated in detail. Importantly, the d Q /d V curve and AC impedance test under variable temperatures were further analyzed to demonstrate the relationship between changes in the discharge platform during the discharge process of the electrode material. The activation energy E a of the interfacial lithium-ion transfer at the electrode interface was evaluated preliminarily. It was confirmed that the MnTeMoO6 @Li2 SiO3 composites exhibited enhanced electrochemical performance with lower activation energy than that of the bare compound.